A mutation in COL4A2 causes autosomal dominant porencephaly with cataracts. Issue 4 (28th December 2015) - Ha, Thuong T.; Sadleir, Lynette G.; Mandelstam, Simone A.; Paterson, Sarah J.; Scheffer, Ingrid E.; Gecz, Jozef; Corbett, Mark A.
Abstract : Mutations in COL4A1 are well described and result in brain abnormalities manifesting with severe neurological deficits including cerebral palsy, intellectual disability, and focal epilepsy. Families with mutations in COL4A2 are now emerging with a similar phenotype. We describe a family with an autosomal dominant disorder comprising porencephaly, focal epilepsy, and lens opacities, which was negative for mutations in COL4A1 . Using whole exome sequencing of three affected individuals from three generations, we identified a rare variant in COL4A2 . This COL4A2 (c.2399G>A, p.G800E, CCDS41907.1) variant was predicted to be damaging by multiple bioinformatics tools and affects an invariable glycine residue that is essential for the formation of collagen IV heterotrimers. The cataracts identified in this family expand the phenotypic spectrum associated with mutations in COL4A2 and highlight the increasing overlap with phenotypes associated with COL4A1 mutations. © 2015 Wiley Periodicals, Inc.